Fatigue, quality of life and metabolic changes in men treated with first-line enzalutamide versus abiraterone plus prednisolone for metastatic castration-resistant prostate cancer (HEAT): a randomised trial protocol. Issue 9 (11th September 2019) - Kvorning Ternov, Klara; Sønksen, Jens; Fode, Mikkel; Lindberg, Henriette; Kistorp, Caroline Michaela; Bisbjerg, Rasmus; Palapattu, Ganesh; Østergren, Peter Busch
Abstract : Introduction: Enzalutamide and abiraterone acetate plus prednisolone (AAP) are used in combination with androgen-deprivation therapy to further suppress the androgen stimulation of metastatic castration-resistant prostate cancer (mCRPC). First-line mCRPC treatment with enzalutamide and AAP yields similar overall survival and radiographic progression-free survival in phase III trials. Thus, treatment selection relies on patient choice, cost and side effects. The aim of this randomised trial is to investigate differences in fatigue, health-related quality of life (HRQoL) and metabolic side effects in men with mCRPC treated with first-line enzalutamide versus AAP. Methods and analysis: In this ongoing open-label randomised (1:1) clinical trial, enzalutamide is compared with AAP as first-line treatment for men with mCRPC. The primary endpoint is fatigue assessed with the questionnaire Functional Assessment of Chronic Illness Therapy-Fatigue version 4. Secondary endpoints are changes in body composition (ie, fat mass, visceral adipose tissue, subcutaneous adipose tissue and lean body mass assessed with dual energy X-ray absorptiometry), glucose metabolism assessed with a 2-hour oral glucose tolerance test, serum lipids, blood pressure and HRQoL assessed with the questionnaire Functional Assessment of Cancer Therapy-Prostate (FACT-P). All study endpoints are assessed at baseline and 12-week postintervention. Blood and urine samples are collected at baseline and at time of progression on allocated treatment for future investigation of predictive and prognostic biomarkers in prostate cancer treatment. The planned sample size is 170 participants. All participants are recruited from Herlev and Gentofte Hospital, Denmark. Estimated last patient's last visit is February 2020. Ethics and dissemination: The study received project approval from the National Committee on Health Research Ethics and Danish Data Protection Agency and Danish Medicines Agency (EudraCT no.: 2017-000027-99). The results of the study will be published in peer-reviewed international journals and will be presented at national and international conferences and symposiums. Trial registration number: Clinicaltrialsregister.eu (2017-000099-27).